(untitled) (Elmergib Journal of Human Sciences, 2025)
This study explores the journeys of European travelers and explorers to the Tripolitania region during the nineteenth century, a period when the province served as one of the most significant geographical and commercial gateways to the interior of the African continent. Tripolitania functioned as a principal departure point toward Sudan, and its strategic location made it a focal hub for European rivalry over trade routes and geographical knowledge. The paper analyzes the attitudes of Tripolitanian rulers toward these travelers: while Yusuf Pasha al-Qaramanli initially welcomed and supported them, the Ottoman authorities later adopted a more cautious approach as they became increasingly aware of the colonial ambitions underlying such expeditions. The research also outlines the major challenges faced by the travelers, ranging from European rivalries and security or tribal threats to religious fanaticism that sometimes compelled them to disguise themselves as Muslims. Furthermore, the study highlights prominent examples of travelers who documented the political, social, economic, and urban life of the region, rendering their accounts vital sources for understanding its history. Ultimately, the research underscores the pivotal role of Tripolitania in modern African history and sheds light on the intersection between European exploration and colonial ambitions.